A Literature Review on Childhood Pneumonia in Bangladesh: Reducing Mortality and Advancing SDG Goals - Alif, Ashrafur Rahman; Rumi, Hasan Mahmud; Emon, Efta Khairul Haque; Tuba, Afnan Islam; Haque, Md Ariful (East West Medical College Journal, 2025)
Background: Pneumonia is the leading cause of under-5 mortality among children worldwide. It is a burden concern, particularly in developing and underdeveloped countries. Despite being a developing country, Bangladesh has shown significant progress in achieving the target goal of the SDG by preventing childhood pneumonia and other causes of under-5 mortality rates. This study aimed to determine the risk factors and strategies that explain the lowering rate of under-five childhood pneumonia in Bangladesh by conducting a comprehensive evaluation and review of the existing epidemiology studies in this field. Method: Our study was conducted using a rigorous methodology. We searched, collected, and evaluated articles that reported the incidence, mortality rate risk factors, and strategies for reducing the rate of under-5 pneumonia in Bangladesh. The search was conducted following the PRISMA guideline, ensuring the thoroughness and reliability of our research. Results: We identified seventeen articles from Bangladesh that met our inclusion criteria. After reviewing the articles, we found that the overall incidence of pneumonia might range from 310 to 511 episodes per 1000 child-years. The mortality rate due to childhood pneumonia is 4 per 1000 live births. The incidence of mortality due to childhood pneumonia varies from paper-12000-16000. Conclusions: Our research goal is to understand the incidence, mortality rate, and pneumonia risk factors in Bangladesh's children under five years old. Reviewing the most recent knowledge would raise awareness of the pneumonia burden in Bangladesh, highlight knowledge gaps for further investigation, and guide policymakers regarding the prevention of pneumonia. There is an annual decline in the prevalence of pneumonia in children, which is noteworthy in Bangladesh. Additionally, we attempted to rule out all strategies that would lessen Bangladesh's childhood pneumonia incidence and under-5 mortality rates. EWMCJ Vol. 13, No. 1, January 2025: 54-64